Perceived stress and sleep quality in young and middle-aged patients with coronary heart disease: the mediating role of perceived social support and mental health literacy - Lu, Ying; Li, Juan; Cui, Zhenzhen; Zheng, Mengzhen; Zhao, Yuqin (Frontiers in Psychology, 2025)
BackgroundGlobally, there is an increasing emphasis on mental health, particularly its role in the recovery of patients with coronary heart disease (CHD). Although previous studies have shown that perceived social support (PSS), mental health literacy (MHL), perceived stress and sleep quality are significantly related, the interaction mechanism remains unclear.ObjectivesTo explore the status of perceived stress, sleep quality, PSS and MHL in young and middle-aged patients with CHD and to test the mediating effect of PSS and MHL between perceived stress and sleep quality.MethodsA convenience sample of 183 young and middle-aged patients with CHD was enrolled between September 2023 and January 2024. Data were collected using a demographic characteristics questionnaire, the mental health literacy scale, the perceived social support scale, the Chinese perceived stress scale, and the Athens insomnia scale. Pearson correlation analysis was conducted to examine relationships between variables, while linear regression analysis was used to assess the predictive effects of perceived stress, PSS, and MHL on sleep quality. Additionally, the PROCESS 4.2 macro for SPSS was employed to explore the mediating roles of PSS and MHL in the relationship between patients’ perceived stress and sleep quality.ResultsCorrelation analysis revealed that perceived stress in young and middle-aged patients with CHD was negatively correlated with MHL (r = −0.381, p < 0.001) and PSS (r = −0.244, p < 0.001), but positively correlated with sleep quality (r = 0.349, p < 0.001). Additionally, the chain mediating role of PSS and MHL (3.93%) between perceived stress and sleep quality was significant.ConclusionPerceived stress not only directly affected sleep quality in young and middle-aged patients with CHD but also could indirectly affect sleep quality through PSS and MHL.